The Relationship Between the Use of Game-Based E-Learning and Interest in Learning IPAS among Fifth-Grade Students at SDN 261 Tarasu - Andi Hardian Dwi Putra; Sitti Jauhar (Journal of Primary Education Innovation and Research, 2025)
This study analyzes the use of game-based e-learning and students’ interest in learning IPAS among fifth-grade students at SD Negeri 261 Tarasu. The purpose of this study was to determine whether there is a relationship between the use of game-based e-learning and the learning interest of fifth-grade students at SD Negeri 261 Tarasu. The approach used in this study was a quantitative approach with a correlational research design. The data sources in this study were 23 fifth-grade students at SD Negeri 261 Tarasu. The data collection techniques used were questionnaires and documentation. The data analysis techniques employed were descriptive statistical analysis and inferential statistical analysis. The results of the descriptive statistical analysis showed that the use of game-based e-learning obtained a mean score of 54.8 and a percentage of 81.97%, which was categorized as very good. Meanwhile, students’ interest in learning IPAS obtained a mean score of 67.2 and a percentage of 84.95%, which was categorized as very good. Based on the results of inferential statistics, rcount ≥ r-table (0.537 ≥ 0.413) at a significance level of 5%. Thus, H1 was accepted and H0 was rejected. In conclusion, there is a positive and significant relationship between the use of game-based e-learning and students’ interest in learning IPAS among fifth-grade students at SD Negeri 261 Tarasu, Kajuara District, Bone Regency, which is classified as moderate in the 0.40–0.599 category